2-pyridinehydroxamic acid (2-pyHA) and its manganese(II) complex: synthesis and characterization / Azlan Shah Mustafa - Mustafa, Azlan Shah (Faculty of Applied Sciences, 2009)
2-pyridinehydroxamic acid (2-pyHA) is prepared by the reaction of hydroxylamine hydrochloride with ethylpicolinate in a 1:2 molar ratio. The manganese(II) complex of 2- pyHA was successfully synthesized giving a moderate yield. The ligand and its complex were characterized using elemental and spectral studies. The spectral data suggests that 2- pyHA act as a bidentate ligand and is coordinated to the metal ion through the O,O coordination mode.